Four-year follow-up of a patient with mixed cardiomyopathy and an implanted cardiac contractility modulation device: a case report - T. M. Uskach; A. A. Safiullina; Yu. Sh. Sharapova; V. A. Amanatova; A. A. Petrukhina; M. I. Makeev; S. N. Tereshchenko (Кардиоваскулярная терапия и профилактика)
The article presents a case report of a 28-year-old male patient with mixed dilated cardiomyopathy: myocardial noncompaction and chemotherapy-related cardiotoxicity, which led to severe heart failure (HF). With optimal drug therapy, the patient was implanted with a cardiac contractility modulation device in order to improve exercise tolerance, quality of life and relieve HF symptoms. Complex therapy has led to significant clinical and echocardiographic improvement. This case demonstrates a 4-year follow-up of a patient with a reduced left ventricular ejection fraction and an implanted cardiac contractility modulation device, whose condition, after several severe HF decompensations, was stabilized.